Didactic Values in the Pantun Seloka of the West Kotawaringin Community - Intang, Darlis; Rapi, Muhammad; Juanda (Universitas Muhammadiyah Malang, 2023)
The Kobar people's pantun seloka contains many local wisdom values. However, the rapid development of human life has affected the existence of seloka rhymes in Kobar society. Society no longer recognizes, understands, and implements its didactic function. Various efforts have been made to save the culture of the people of Kobar. This study aimed to find the didactic value in the Kobar verses of Central Kalimantan Province. This research is a type of qualitative research with a qualitative descriptive approach. A qualitative descriptive approach produces a good description of the didactic values in the Kobar seloka rhyme. Data collection techniques used literature review procedures, observation methods, note-taking techniques, and reflective introspection. The data analysis technique in this study uses the interactive model. The results of the study found that there are four classifications of values contained in the Kobar seloka pantun, namely: (a) entertainment value, (b) the vitality value of life, (c) spiritual value, and (d) religious values. Within these four value categories, it was concluded that the most didactic values were found in the spiritual value category, namely: (a) social knowledge (muamalah), which is divided into three, namely (1) husband-wife relationship; (2) the relationship between parents and children; and (3) human relations; (b) Indigenous and Cultural knowledge; and (e) natural-environmental knowledge. Then, the category of religious values, namely: (a) belief in Allah SWT and His Messenger; (b) belief in the afterlife; and (c) following religious orders. Furthermore, didactic values are also found in the category of life vitality values, namely: (a) working together and (b) working together. Finally, the didactic value is found in the entertainment value, namely the sense of togetherness in the community. The implications of this research are on the preservation of local culture in Indonesia, especially sloka rhymes. In addition, the results of this study can be used by teachers at school to build character in students at school.